Systematic identification of allosteric effectors in Escherichia coli metabolism - Christoph Heinrich Gruber; Elad Noor; Marieke Francisca Buffing; Uwe Sauer (Proceedings of the National Academy of Sciences, 2025)
Recent physical binding screens suggest that protein–metabolite interactions are more extensive than previously recognized. To elucidate the functional relevance of these interactions, we developed a mass spectrometry–based screening method for higher throughput in vitro enzyme assays. By systematically quantifying the effects of 79 metabolites on the activity of 20 central Escherichia coli enzymes, we not only assess functional relevance but also gauge the depth of the current understanding of regulatory interactions within one of the best-characterized networks. Our identification of 50 inhibitors and 14 activators not only expands the range of known input signals but also uncovers novel regulatory logic. For instance, we observed that AMP inhibits malic enzyme to safeguard the cyclic operation of the tricarboxylic acid cycle, and erythrose-4-phosphate inhibits 6-phosphogluconate dehydrogenase to redirect flux from the pentose phosphate pathway into the Entner–Doudoroff pathway. Discrepancies between our standardized assays and existing database entries suggest that many previously reported interactions might occur only under specific, often nonphysiological conditions. Our dataset represents a systematically determined functional protein–metabolite interaction network, establishing a baseline for allosteric regulation in central metabolism. These results enhance our understanding of the regulatory logic governing metabolic processes and underscore its significance in cellular adaptation and growth.